2019
DOI: 10.1016/j.wjorl.2017.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Is tinnitus a major concern in individuals with auditory neuropathy spectrum disorder? – Questionnaire based study

Abstract: ObjectiveOur study attempted to determine if tinnitus is a major concern in individuals with auditory neuropathy spectrum disorder (ANSD). The study also attempted to determine if pure tone average (PTA), speech identification scores (SIS), or reported duration of hearing loss could predict the tinnitus severity and functional handicap in adults with ANSD.MethodsTinnitus functional index (TFI) and tinnitus severity index (TSI) were administered on all the 40 participants diagnosed with ANSD.ResultsThe mean TFI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…This was closely followed by those who described it as moderate. In a multi centered hospitalbased study and a questionnaire-based study by Okhakhu et al [31] and Prabhu [42] respectively; it was found that the degree of tinnitus distress was scored as moderate in many of tinnitus patients. This further corroborated the report that most patients seek for specialist care when the symptom has already caused some form of disturbance or became associated with other ear symptoms [23].…”
Section: Discussionmentioning
confidence: 99%
“…This was closely followed by those who described it as moderate. In a multi centered hospitalbased study and a questionnaire-based study by Okhakhu et al [31] and Prabhu [42] respectively; it was found that the degree of tinnitus distress was scored as moderate in many of tinnitus patients. This further corroborated the report that most patients seek for specialist care when the symptom has already caused some form of disturbance or became associated with other ear symptoms [23].…”
Section: Discussionmentioning
confidence: 99%